A new Peruvian species and new records of the genus Elmas Blackwelder (Coleoptera: Staphylinidae) - Rodríguez, Maryzender; Asenjo, Angélico; Pérez, Luis (Zootaxa, 2019)
Elmas gorky Rodríguez et al. new species, is described from the department of Madre de Dios in southeastern Peru. Major diagnostic features are photographed and illustrated. New records are provided for Elmas gigas Ashe & Chatzimanolis, Elmas lescheni Ashe & Chatzimanolis and Elmas strigella (Bernhauer).